Salud sexual reproductiva y su relación con el desarrollo de embarazos en adolescentes de la comunidad de Guanujo, marzo - agosto 2024. - Paguay Vinueza, María Cristina (2024)
The present curricular research work emphasized the relationship between sexual and reproductive education and the development of adolescent pregnancies, which represent a serious public health problem, However, the strategies implemented to reduce it have achieved little or nothing in the fight against problematic situation. This research with quantitative, basic and field approach with level of descriptive study, prospective and transversal temporal dimension had as main objective to analyze the impact of reproductive sexual education on the development of adolescent pregnancies in the community of Guanujo, March - August 2024. Data collection was done by implementing a survey, whose instrument was a questionnaire of 17 objective questions aimed at obtaining relevant information on the subject matter under investigation and through the research modality of analysis and synthesis, it was concluded that 66% of adolescents are unaware of health policies for Prevention of early pregnancy, with the taboo being the main risk factor making it impossible to acquire information on the subject.